V.2 - Shah, A. M. (ed.); Baviskar, B. S. (ed.); Ramaswamy, E. A.(ed.) (New Delhi, 1996)
This book-the second in the series of five volumes in honour of eminent sociologist and social anthropologist, M.N. Srinivas-focuses on the changing status of women in Indian society. The distinguished contributors cover a wide range of issues concerning women. These include the gender bias in development policies; women's participation in production processes in rural as well as urban settings; socio-cultural dimensions of women's education during the colonial period; and the deeper structures and processes which lie behind female infanticide in northern and western India. Of particular note is the methodological approach adopted by the contributors. Moving beyond the usual internalist and externalist approaches to the gender question, the discussion focuses on the interplay between the familial domain and the external forces that impinge on it. Various essays explore issues related to the survival and nurturance of the girl child, her access to education and participation in productive activity and, most importantly, her right to natal property. This discussion is located in the context of external developments such as improved irrigation and the commercialization of agriculture, shifts in land ownership patterns and the dynamics of caste affiliations. Based on primary as well as secondary data, these cogently argued essays provide a valuable framework to assess the process of reform and change in Indian society within a gender perspective. This volume will interest all those involved in the fields of gender studies, social change, sociology and social anthropology.
Keywords: Social change